The impact of what is not measured. Principal underlying factors in the UNDP Gender Inequality Index - Zamora Torres, América Ivonne; Marín Leyva, René Augusto; Díaz Barajas, Yesica (FEMERIS: Revista Multidisciplinar de Estudios de Género, 2022)
Currently, there are still significant inequalities in the conditions in which men and women live and act in most of the countries of the world, which as a whole, constitute important gender gaps in various areas, that do not allow countries to benefit with the maximum potential of both genders in their development processes, also preventing women from reaching their maximum human potential. The objective of this paper is to identify, through the generation of empirical evidence, the factors that impact gender inequality in 161 countries by the year 2020, integrating dimensions to the proposal of the Gender Inequality Index (GII) developed by the United Nations Development Program (UNDP), which would allow addressing the problem in a more comprehensive way. To achieve this objective, it was used a verifiable factor analysis method, considering the variables that currently make up the three dimensions of the GII in 2020, finding -according with the theory analyzed- the role of the female gender as first underlying factor, which frames women as main responsible for the home and reproductive sphere, acting as a first form of exclusion that prevents them from joining the social, productive and political spheres with the same conditions of freedom and opportunities that men.